Studi Komparasi Kinerja Profitabilitas dan Earning Per Share PT Bank Central Asia Tbk Sebelum dan Setelah Menerapkan Mobile Banking - Eltasya Sifra Mevia Simanungkalit; Endang Hatma Juniwati; Banter Laksana (Indonesian Journal of Economics and Management, 2022)
This investigation was done to compare the performance of PT Bank Central Asia Tbk's profitability and earnings per share (EPS) before and after the implementation of mobile banking. In this study, financial statements from 2008 to 2017—five years before and five years after the usage of mobile banking—are used. The implementation of mobile banking in PT Bank Central Asia Tbk's services has had an impact on a number of areas, including profitability and earnings per share (EPS) performance. These areas include an increase in return on assets (ROA), a decrease in return on equity (ROE), and an increase in earnings per share (EPS). All of the variables were distributed regularly, according to the findings of the normality test. Before and after the implementation of mobile banking, there is a considerable variation in the Return on Assets (ROA) ratio. There is no notable difference in the Return on Equity (ROE) ratio. While there is a sizable variation in EPS between before and after the implementation of mobile banking